Analisis Kuat Tekan dan Workability Beton dengan Penambahan Silica Fume dan Variasi Tras Lompotoo Sebagai Substitusi Parsial Agregat Halus - Rayhan Putri Maiyo; Kasmat Saleh Nur; Komang Arya Utama (Transbahasa, 2026)
The use of pozzolanic materials, such as silica fume and Lompotoo trass, aims to enhance concrete performance while reducing the use of sand as a fine aggregate. Lompotoo trass is a material with a high fineness, making it suitable for partial substitution for fine aggregate. This study aims to analyze the effect of adding silica fume and varying the percentage of Lompotoo trass as a partial substitution for fine aggregate on the compressive strength and workability of concrete. The testing was conducted by producing four mix variations: normal concrete and concrete with partial substitution of Lompotoo trass for fine aggregate at 25%, 50%, and 75%. Each variation of Lompotoo trass substitution was combined with the addition of 10% silica fume. In general, changes in concrete characteristics were observed across all mix variations. The slump value showed a decreasing trend as the percentage of Lompotoo trass substitution increased. On the other hand, the compressive strength of normal concrete of f’c 30.34 MPa increased to f’c 32.16 MPa at 25% trass substitution, f’c 32.97 MPa at 50% substitution, and reached f’c 36.65 MPa at 75% substitution. These results indicate that the use of Lompotoo trass combined with silica fume enhances the compressive strength of concrete, although it is accompanied by a reduction in workability.